The Organic Interrelation Between Legal Requirements and Citizens’ Moral Responsibility in the Electoral Process - Dadajonova Feruza Abduaziz Qizi (Universitas Muhammadiyah Sidoarjo, 2026)
This study investigates the interdependent relationship between legal regulation and citizens' moral responsibility in electoral processes, addressing the critical challenge that formal electoral laws alone cannot guarantee democratic legitimacy without corresponding ethical engagement from the electorate. The research aims to theoretically and practically substantiate how legal requirements and moral consciousness function as mutually reinforcing mechanisms in ensuring free, fair, and transparent elections. Employing a comprehensive methodological framework, the study integrates comparative analysis of legal systems, structural-functional approaches to electoral institutions, content analysis of legislative documents and academic literature, and sociological observation of civic behavior patterns during electoral processes. The analysis reveals that while legal norms provide essential procedural frameworks—including voting freedom, equality principles, and transparency mechanisms—their effectiveness critically depends on citizens' internalization of ethical values such as integrity, civic duty, responsibility, fairness, and political awareness. The principal finding demonstrates that electoral violations including corruption, vote-selling, and manipulation primarily stem from insufficient moral responsibility rather than legislative deficiencies, even in contexts with advanced electoral codes and technological safeguards. The novelty of this research lies in its systematic integration of legal and socio-ethical dimensions within electoral analysis, challenging purely normative approaches by establishing electoral culture as a key socio-legal factor bridging formal regulation and civic ethics. The study's implications extend to democratic governance theory and electoral reform policy, recommending continuous electoral education systems, enhanced digital civic outreach, strengthened public oversight mechanisms, and youth engagement strategies to cultivate the moral consciousness necessary for sustainable democratic institutionsKeywords : Electoral Legitimacy, Civic Morality, Legal-Ethical Complementarity, Democratic Governance, Political CultureHighlight : Legal norms require moral responsibility to prevent electoral violations like corruption and manipulation. Citizens' ethical awareness directly determines transparency, fairness, and legitimacy of democratic elections. Electoral culture integrating legal consciousness and civic duty strengthens public trust in institutions.